2012
DOI: 10.1371/journal.pone.0041424
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial Stromal Cells of Women with Recurrent Miscarriage Fail to Discriminate between High- and Low-Quality Human Embryos

Abstract: BackgroundThe aetiology of recurrent miscarriage (RM) remains largely unexplained. Women with RM have a shorter time to pregnancy interval than normally fertile women, which may be due to more frequent implantation of non-viable embryos. We hypothesized that human endometrial stromal cells (H-EnSCs) of women with RM discriminate less effectively between high-and low-quality human embryos and migrate more readily towards trophoblast spheroids than H-EnSCs of normally fertile women.Methodology/Principal Findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
131
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(134 citation statements)
references
References 28 publications
3
131
0
Order By: Relevance
“…RSA is one of the most common complications associated with early pregnancy and remains a challenge in gynecology (Jauniaux et al, 2006). Different potential etiologic factors have been implicated in this condition, such as endocrine regulation, autoimmune reaction, thrombophilia, environmental, psychological, and genetic background, and viral infections (Bergant et al, 1997;Bussen et al, 1999;Li et al, 2002;Quenby et al, 2005;Weimar et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…RSA is one of the most common complications associated with early pregnancy and remains a challenge in gynecology (Jauniaux et al, 2006). Different potential etiologic factors have been implicated in this condition, such as endocrine regulation, autoimmune reaction, thrombophilia, environmental, psychological, and genetic background, and viral infections (Bergant et al, 1997;Bussen et al, 1999;Li et al, 2002;Quenby et al, 2005;Weimar et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, ESCs of women with RM showed prolonged receptivity (super receptivity), with low selectivity for low quality embryos [40] . A recent study showed that the migration of ESCs from RM women was similar in the presence of low-quality or high quality embryos [41] .…”
Section: Failure Of Embryo Selectionmentioning
confidence: 99%
“…The decidual milieu is overall favourable for trophoblast expansion and migration [12,13]. Recently, early decidua has been identified as a 'sensor' of human embryo quality [14,15]. It was found that the decidual cells could discriminate between 'good' and 'bad' quality embryos, except in the case of cells derived from women with recurrent pregnancy loss in whom the discriminatory capacity was absent [16].…”
Section: Implantation-specific Microenvironmentsmentioning
confidence: 99%